Effect of perspired moisture and material properties on evaporative cooling and thermal protection of the clothed human body exposed to radiant heat. Issue 18 (September 2019) - Guan, Manhao; Psikuta, Agnes; Camenzind, Martin; Li, Jun; Mandal, Sumit; Michel Rossi, René; Annaheim, Simon
Perspired moisture plays a crucial role in the thermal physiology and protection of the human body wearing thermal protective clothing. Until now, the role of continuous sweating on heat transfer, when simultaneously considering internal and external heat sources, has not been well-investigated. To bridge this gap, a sweating torso manikin with 12 thermal protective fabric systems and a radiant heat panel were applied to mimic firefighting. The results demonstrated how the effect of radiant heat on heat dissipation interacted with amount of perspired moisture and material properties. A dual effect of perspired moisture was demonstrated. For hydrophilic materials, sweating induced evaporative cooling but also increased radiant heat gain. For hydrophilic station uniforms, the increment of radiant heat gain due to perspired moisture was about 11% of the increase of heat dissipation. On the other hand, perspired moisture can increase evaporative cooling and decrease radiant heat gain for hydrophobic materials. In addition to fabric thermal resistance ( Rct ) and evaporative resistance ( Ret ), material hydrophilicity and hydrophobicity, emissivity and thickness are important when assessing metabolic heat dissipation and radiant heat gain with profuse sweating under radiant heat. The results provide experimental evidence that Rct and Ret, the general indicators of the clothing thermo-physiological effect, have limitations in characterizing thermal comfort and heat strain during active liquid sweating in radiant heat. This paper offers a more complete insight into clothing thermal characteristics and human thermal behaviors under radiant heat, contributing to the accurate evaluation of thermal stress for occupational and general individuals.